Estudio de la capacidad de gestión del talento humano para asumir competencias del Gobierno Autónomo Descentralizado del Cantón Bolívar - Basurto Rendón, Carlos Fabian (2016)
This research was conducted to know the problems that exist in public institutions in our country and in turn give a solution, applying the knowledge acquired in the classroom, research is based on diagnosing the ability of human talent management to assume powers of the Autonomous Government Decentralized canton Bolivar in accordance with the Constitution and the Organic Code of Territorial Organization Autonomy and Decentralization, research methods applied were the inductive basis of the specific information to argue the general idea, and deductive was used to reach conclusions that helped to develop alternative solutions to improve the management of human resources in the institution, and an interview was applied to the mayor in order to know the competitions that has assumed the DAG, and gather more data supporting the research, direct observation it was known the activities developed in each of the areas of work which established appropriate guidelines for the solution of the problem, with the techniques applied was achieved detect the degree of complexity of each competition when being executed, the activities developed by each department allowed to develop a matrix sizing in which the days running each of them were determined, considering it necessary to develop a process evaluation human talent in order to optimize the performance of administrative management.